Asia's Role in the New United States Export Economy - William E. James; Shiela Camingue (Asian Development Bank (ADB), 2011)
"William E. James and Shiela Camingue examine the composition and prospects for growth of net exports of the United States (US) to the world and to developing Asia. They find that much of the apparent shift in export product shares was a result of the worldwide collapse in demand for high-technology products, particularly new aircraft and information technology products. Nonetheless, India, ASEAN-10, and the newly industrialized economies are destinations for US high-technology products to an even greater extent than for the world as a whole. In contrast, the People's Republic of China tends to import a lower portion of high-technology products but a larger share of agriculture-related and raw materials and energy products than the world as a whole."
hdl:11540/2054
Keywords: 330; Außenhandelsstruktur; USA; Export; Asien; Welt